My proof has a hole there, wonder if anyone can help me fill it in?

$$f^*(w \wedge \theta) = (f^*w) \wedge (f^* \theta)$$

By definition,

$$f^*w(x) = (df_x)^*w[f(x)].$$

So I understand $w[f(x)]$ as the $p$-tensor eats a $p$-vector $f(x)$.

The main problem is, that I don't think the function $f$ whose range is a $p$-dimensional vector space can distribute into $w$ and $\theta$ respectively, as what I hope to reach after the question marks.

In order to make $w \otimes \theta$ makes sense on the left hand side, we want $w$ to eat an $m$-vector and $\theta$ to eat an $n$-vector, where $m+n=p$. Hence, how can each $w$ and $\theta$ eats a $p$-vector $f$?

\begin{eqnarray} f^*(w \wedge \theta) & = &(df_x)^* (w \wedge \theta) (f)\\ & = &(df_x)^* \operatorname{Alt}(w \otimes \theta) (f)\\ & = &(df_x)^* \frac{1}{p!}\sum_{\pi \in S_p}(-1)^\pi(w \otimes \theta)^\pi (f)\\ & = & ???\\ & = &\frac{1}{p!}\sum_{\pi \in S_p}(-1)^\pi((df_x)^*w(f) \otimes (df_x)^*\theta(f))^\pi\\ & = & \operatorname{Alt}[(df_x)^*w(f) \otimes (df_x)^*\theta(f)]\\ & = &(df_x)^*w(f) \wedge (df_x)^*\theta(f)\\ & = &(f^*w) \wedge (f^* \theta). \end{eqnarray}

  • $\begingroup$ I'm confused, I would think $f$ is a function so $f^* \omega$ is a pull-back under $f$ of a form in the range of $f$ to a new form $f^* \omega$ in the domain of $f$. To understand it, I would evaluate on an appropriate tuple of vectors at a given point and work through the push-forward feeding into the range form... maybe I have a different problem in mind? $\endgroup$ – James S. Cook Jul 29 '13 at 23:26
  • $\begingroup$ Hi @JamesS.Cook, I think you are right, and I think my understanding to $w[f(x)]$ is wrong. How does $w[f(x)]$ work? $\endgroup$ – WishingFish Jul 29 '13 at 23:28
  • $\begingroup$ I wrote up an answer to a question I think you want to ask... $\endgroup$ – James S. Cook Jul 29 '13 at 23:49

Suppose $\omega$ and $\phi$ are one-forms on $N$ and $f: M \rightarrow N$ is a function. The form $\omega \wedge \phi$ is a two-form on $N$ and the pull-back under $f$ would be denoted $f^*(\omega \wedge \phi)$ it is a two-form on $M$. In particular, the definition can be made precise in terms of two vectors at $p \in M$. \begin{align} f^*(\omega \wedge \phi)(v,w) &= (\omega \wedge \phi) (d_pf(v),d_p(w)) \\ &= (\omega \otimes \phi- \phi \otimes \omega) (d_pf(v),d_p(w)) \\ &= (\omega \otimes \phi)(d_pf(v),d_p(w))- (\phi \otimes \omega) (d_pf(v),d_p(w)) \\ &= \omega (d_pf(v) \phi(d_p(w))- \phi (d_pf(v))\omega (d_p(w)) \\ &= (f^*\omega)(v) (f^*\phi)(w)- (f^*\phi)(v)(f^*\omega)(w) \\ &= (f^*\omega \otimes f^*\phi)(v,w)- (f^*\phi \otimes f^*\omega)(v,w) \\ &= (f^*\omega \otimes f^*\phi - f^*\phi \otimes f^*\omega)(v,w) \\ &= (f^*\omega \wedge f^*\phi)(v,w) \end{align} This holds for all $v,w \in T_pM$ hence the identity $f^*(\omega \wedge \phi) = f^*\omega \wedge f^*\phi$ holds. This argument can be generalized for $\omega$ a $k$-form and $\phi$ a $r$-form, you just have to sort through the antisymmetrization. Looks like you may already have those tools ready to use, so I hope this case suffices to get you started.

  • $\begingroup$ Dear James - thank you. You look right, but you are not using the definition I was given... > $$f^*w(x) = (df_x)^*w[f(x)].$$ :-P $\endgroup$ – WishingFish Jul 30 '13 at 0:48
  • $\begingroup$ @WishingFish I think I am... $(df_x)^*$ is the pull-back of the $df_x$ map. How does that work? Well, $(df_x)^*(w[f(x)])(v) = w[f(x)](df_x(v))$. The $f(x)$ in the $w[f(x)]$ means you are using the form $w$ at $f(x)$. I suppressed the point-dependence in my answer. $\endgroup$ – James S. Cook Jul 30 '13 at 1:36
  • $\begingroup$ Hi James, that is exactly where confuses me - I never get what $w[f(x)]$ really is. My guess is that $w$ is a $p$-tensor, and $f(x)$ fed it assuming $f$ evaluated at $x$ is a $p$-tuple vector. So what do you mean by "The $f(x)$ in the $w[f(x)]$ means you are using the form $w$ at $f(x)$"? I think you are right and I was wrong, so I am trying to get your point! I used a new question, here: math.stackexchange.com/questions/455322/definition-of-pullback $\endgroup$ – WishingFish Jul 30 '13 at 1:56
  • $\begingroup$ @WishingFish right, I do believe that notation indicates using the form $w$ at the point $f(x)$. I'll look at your other question shortly... $\endgroup$ – James S. Cook Jul 30 '13 at 4:51
  • $\begingroup$ Thank you so much for your help, James! $\endgroup$ – WishingFish Aug 14 '13 at 6:13

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.